Nexus Between Technology Innovation in Civil Engineering and Educational Sustainability in Nigeria - Theophilus, Akinbuluma Ayodeji (Universitas Sebelas Maret, 2022)
Abstract: Innovation is very imperative for the educational development of any nation. This article assessed the nexus between Technology Innovation in Civil Engineering and Educational Sustainability in Nigeria. The focus of this study was to examine the Education of Nigerian civil Engineers in Nigeria and investigated factors challenging technological innovation in Civil Engineering Education. It was discovered that the level of innovation and technology integration in Civil Engineering Education in Nigeria is low. Factors posing challenges to innovation in Nigeria includes institutional framework; human capital; research/innovation infrastructure; and sophisticated business community. This article recommended that the Government should evolve policies that would address the challenges in technological innovations Innovation. Government should provide adequate modern research facilities that would drive research in civil engineering at universities and in other tertiary institution in Nigeria. Modern research facilities should be established and human capital developed. The study concluded that if science and technology are well taught and adequate facilities are provided for the study of civil Engineering and other Engineering related study healthy and prosperous Nigeria is inevitable.